From Angiotensin IV to Small Peptidemimetics Inhibiting Insulin-Regulated Aminopeptidase - Hallberg, Mathias; Larhed, Mats (Frontiers in Pharmacology, 2020)
It was reported three decades ago that intracerebroventricular injection of angiotensin IV (Ang IV, Val-Tyr-Ile-His-Pro-Phe) improved memory and learning in the rat. Several hypotheses have been put forward to explain the positive effects of the hexapeptide and related analogues on cognition in various experimental models. In 2001, it was proposed that the insulin-regulated aminopeptidase (IRAP) is a main target for Ang IV and that Ang IV serves as an inhibitor of the enzyme. The focus of this minireview is the efforts to stepwise transform the hexapeptide into more drug-like Ang IV peptidemimetics serving as IRAP inhibitors. Moreover, the discovery of IRAP inhibitors by virtual and substance library screening and direct design applying knowledge of the structure of IRAP and of related enzymes is briefly presented.